Proyeksi Kebutuhan Pengembangan Terminal Building Bandar Udara (Studi Kasus: Bandar Udara Internasional Sultan Syarif Kasim II Pekanbaru) - Bismo Anggoro; Ari Sandhyavitri; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study aims to investigate whether or not the extents of Sultan Syarif Kasim II International Airport which is located in Pekanbaru need to be developed. Using linear regression method, this study forecasted that there will be a need to develop terminal building area up to 63.414m2 with the capacity of passengers about 6.693.746 every year and it will be accommodated approximately 3724 passengers on peak hour in 2035. The development of terminal building area is bigger than existing area in 25.779 m2 and the capacity of passengers is 3,2 millions every year while accommodating 1866 passengers on peak hour.Keywords : Terminal Buiding, Development